PERANAN PENGENDALIAN INTERNAL ATAS PENJUALAN KREDIT PUSBAHNAS KBM - Aaron Leonard Alfeus; Melinda Malau (Buletin Ekonomi, 2018)
Every company or organization that is established must have a goal to be achieved by effective and efficient manner. It also applies to all types of organizations such as the engaged state, in politics, in economics, in business, in social culture - such as pendidikam and health - nonprofit organizations, civil society organizations and even in religious environments though. Many products produced by PT Perhutani (Persero) which one of them in the field of Pusat Perlebahan Nasional or abbreviated Pusbahnas. The activities undertaken in Pusbahnas is processing local honey and honey purchased through partners through several methods such as open auctions, direct election, appointment, direct procurement and self-management. In this case PT Perhutani especially those Pusbahnas choose cash sales method and no longer use credit sales, internal controls and procedures for the sale of merchandise is very important for the company to increase its sales. The purpose of this report is to determine the procedure on credit sales Pusbahnas, determine the method used to increase sales, and to determine the role of internal control in credit sales Pusbahnas KBM. The results of the field work practice carried out showed that the internal control over credit sales at PT Perhutani Pusbahnas still needs to separate work functions and additional control to avoid deviations.Keywords: Internal Control, Procedure, Sales, Credit Sales